2013
DOI: 10.4161/mabs.26396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a tail piece cysteine deletion on biochemical and functional properties of an epidermal growth factor receptor-directed IgA2 m(1) antibody

Abstract: Antibodies of human IgA isotype are critical components of the mucosal immune system, but little is known about their immunotherapeutic potential. Compared with IgG antibodies, IgA molecules carry a C-terminal tail piece extension of 18 amino acids with a free cysteine at position 471. This cysteine is required for the formation of dimeric IgA antibodies, but may impair molecular characteristics of monomeric IgA antibodies as therapeutic reagents. Thus, we generated and characterized a d471-mutated antibody ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…A analogous phenomenon was noticed by Brunke et al when comparing Nglycans from 2 IgA2m1 antibodies produced in CHO-K1, one a wildtype sequence and the other a mutated version in which the cysteine in the tailpiece had been deleted. 23 Here as well, the IgA with a tailpiece mutation contained significantly lower high-mannose N-glycans compared to the wild-type IgA. It is quite conceivable, as suggested by these authors, that interfering with intracellular tailpiece interaction by deletion of the penultimate cysteine or even the complete tailpiece may alter the intracellular fate of the IgA molecule.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…A analogous phenomenon was noticed by Brunke et al when comparing Nglycans from 2 IgA2m1 antibodies produced in CHO-K1, one a wildtype sequence and the other a mutated version in which the cysteine in the tailpiece had been deleted. 23 Here as well, the IgA with a tailpiece mutation contained significantly lower high-mannose N-glycans compared to the wild-type IgA. It is quite conceivable, as suggested by these authors, that interfering with intracellular tailpiece interaction by deletion of the penultimate cysteine or even the complete tailpiece may alter the intracellular fate of the IgA molecule.…”
mentioning
confidence: 55%
“…22 As expression of an anti-HER2 IgA2m2 lacking the penultimate cysteine or even the entire heavy chain tailpiece yielded mostly monomeric species, it can be concluded that dimers and polymers were primarily due to tailpiece interactions probably involving disulfide bridge formation between the penultimate cysteines. 23 The non-reducing SDS-PAGE revealed that especially the IgA2m1 preparation seemed to be unstable as the profile displayed a variety of protein species in addition to the full-length protein, species most likely representing antibodies lacking one light chain or species consisting of homodimers of heavy and light chains. 21 However, SEC proved conclusively that the anti-HER2 IgA antibodies were intact.…”
Section: Her2mentioning
confidence: 99%
“…1. Further cloning, production, purification, as wells as the determination of antibody concentrations, specific production rates, gel electrophoresis, Western blotting, as well as the functional characterization were done as described earlier (13,35).…”
Section: Cell Linesmentioning
confidence: 99%
“…Twenty-four hours later cells were yielded by trypsinization, stained with Annexin-FITC/PI kit (BD) and analyzed by immunofluorescence analyses. Preparation and engagement of effector cells was analyzed in 51 chromium release assays as described earlier (13,35). ASGPR-mediated uptake of antibodies was investigated using BHK cells, transfected with pCMV6-AC plasmid encoding ASGPR1 (OriGene) and Lipofectamine 2000 (Life Technologies).…”
Section: Cell-based Assaysmentioning
confidence: 99%
“…To make the 9A antibody, synthetic genes encoding the V H domain, C H 1 domain, and hinge region sequences of 9C12 were combined with C α 2 and C α 3 domains of human IgA1 and expressed in 293F cells from a bicistronic protein expression vector pBUD.CE4.1 (Invitrogen), which also carried the 9C12 light chain (11). The C α 2 and C α 3 domain boundaries were based on the published IgA Fc crystal structure and lack the C-terminal 18 amino acids normally found in IgA (33). These residues have previously been shown not to be necessary for FcαRI interaction, which overlaps the TRIM21 binding site.…”
Section: Methodsmentioning
confidence: 99%